Multifaceted application of nanoparticle-based labeling strategies for stem cell therapy. (October 2020) - Ma, Ming; Shu, Yimeng; Tang, Yaohui; Chen, Hangrong
Graphical abstract: Highlights: Nanoparticle-based labeling agents can be used to monitor the location, survival, and differentiation of stem cells in the therapeutic process. Nanoparticle-based labeling agents can promote the survival, directed differentiation, and homing of transplanted stem cells. Nanoparticle-based theranostic labeling is a newly developed strategy that can co-deliver both imaging and treatment functions into stem cells. Theranostic labeling can meet multiple demands simultaneously for high-quality stem cell therapy. Abstract: Stem cell therapy can overcome many unmet clinical challenges that have proven intractable with traditional medicine and treatment strategies because of their strong ability to recover and regenerate injured tissue. Nanoparticle-based labeling agents, in combination with current imaging technologies, have been used to monitor the location, migration, survival, and differentiation of transplanted stem cells in therapeutic processes to fully understand their fates in vivo . In addition, various kinds of functional nanoparticles can exert unique biological effects on stem cells to overcome some problems of current stem cell therapy involving cell homing, survival, retention, and directional differentiation. Moreover, nanoparticle-based theranostic labeling, in which both imaging and treatment modalities are delivered with the stem cells, has emerged as a new strategy to enhance the therapeutic effect of stem cells and shows great potential for future stem cell therapy. The aim of this review is to describe the current roles played by nanoparticles in cell tracking, cell fate regulation, and theranostic labeling in stem cell therapy. Important issues and perspectives on the potential growth of this area are also critically discussed.